2021
DOI: 10.1111/jvh.13608
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor agonist for the treatment of chronic hepatitis B: A safety study

Abstract: The nuclear farnesoid X receptor (FXR) regulates bile acid homeostasis and is a drug target for metabolic liver diseases. FXR also plays an important role in hepatitis B virus (HBV) DNA transcription. In vitro and in mice, FXR agonist treatment leads to inhibition of viral replication and a decline in viral proteins, pregenomic RNA (pgRNA) and HBV DNA levels. We aimed to translate this to a clinical use by primarily evaluating the safety and secondary the anti-viral effect of Vonafexor, a FXR agonist, in chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Vonafexor was well tolerated overall with moderate gastrointestinal adverse effects (pruritus occurred in ~60% of subjects with twice-daily treatment compared with 16% in subjects with once-daily treatment). Vonafexor alone or combined with interferon-α2a showed an anti-viral effect by reducing HBV markers [ 252 ]. In non-diabetic NAFLD patients, a 4-weeks of treatment with the non-steroidal FXR agonist PX-104 improved liver enzymes and insulin sensitivity with no serious adverse events.…”
Section: Fxr As a Therapeutic Target?mentioning
confidence: 99%
“…Vonafexor was well tolerated overall with moderate gastrointestinal adverse effects (pruritus occurred in ~60% of subjects with twice-daily treatment compared with 16% in subjects with once-daily treatment). Vonafexor alone or combined with interferon-α2a showed an anti-viral effect by reducing HBV markers [ 252 ]. In non-diabetic NAFLD patients, a 4-weeks of treatment with the non-steroidal FXR agonist PX-104 improved liver enzymes and insulin sensitivity with no serious adverse events.…”
Section: Fxr As a Therapeutic Target?mentioning
confidence: 99%
“…In addition, OCA stops HIV-1 particle accumulation within the liver cells (Zhou et al 2019 ). A recent study displayed that FXR agonists potentially affect the proliferation of the hepatitis B virus (HBV) (Erken et al 2021 ). A double-blind placebo-controlled trial of 73 cases with HBV infection treated with FXR agonists for 35 days demonstrated that these agents efficiently lessened the hepatitis B surface antigen (HBsAg) level relative to the placebo impact (Erken et al 2021 ).…”
Section: Antiviral Effects Of Ocamentioning
confidence: 99%
“…A recent study displayed that FXR agonists potentially affect the proliferation of the hepatitis B virus (HBV) (Erken et al 2021 ). A double-blind placebo-controlled trial of 73 cases with HBV infection treated with FXR agonists for 35 days demonstrated that these agents efficiently lessened the hepatitis B surface antigen (HBsAg) level relative to the placebo impact (Erken et al 2021 ). FXR agonists interact with HBV viral proteins preventing their transcription and triggering off the reduction of HBV viral protein (Erken et al 2021 ).…”
Section: Antiviral Effects Of Ocamentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple novel therapeutics, broadly classified as virus-targeting agents and immunomodulators, are being actively investigated as strategies for achieving functional cure [ 5 ]. Virus-targeting agents inhibit different steps of the HBV lifecycle and agents in development include: 1) entry inhibitors: which inhibit HBV docking and hepatocyte entry [ 6 ]; 2) polymerase inhibitors: which inhibit HBV polymerase competitively (conventional NAs) or non-competitively (novel active site polymerase inhibitor nucleotide) [ 7 ]; 3) RNA silencers: which inhibit HBV messenger RNA (mRNA) translation and viral protein production [ 8 ]; 4) capsid assembly modulators: which inhibit HBV nucleocapsid assembly and pregenomic RNA encapsidation [ 9 ]; 5) viral protein export inhibitors: which inhibit HBV antigen release from hepatocytes [ 10 , 11 ]; and 6) farnesoid X receptor (FXR) agonist: which reverses the interaction between FXR and the HBV X protein to interfere with transcription regulation [ 12 ]. Immunomodulators utilize an alternative strategy which is different from virus-targeting agents.…”
Section: Introductionmentioning
confidence: 99%